Proceedings of the International Conference on Youth 2013 (ICYOUTH 2013) - Institute For Social Science Studies (Institute For Social Science Studies, 2013)
The Proceedings of the International Conference on Youth 2013, held from 29 to 31 October 2013 at Mines Wellness Hotel, Sri Kembangan, Selangor, Malaysia, and organized by the Institute for Social Science Studies.